Strategic Evaluation and Analysis of The Pharmacy Logistics Management System at The Tamalate Community Health Center in Makassar City - Kahfi, Muhammad; Nildawati, Nildawati; Wahyuddin, Nur Rahmah (Universitas Islam Negeri Alauddin Makassar, 2026)
Quality primary healthcare services depend heavily on the availability of safe, high-quality, and affordable pharmaceutical preparations. This study aims to conduct an in-depth analysis of the pharmaceutical logistics management system at the Tamalate Community Health Center in Makassar City in 2025. The method used is descriptive qualitative with data collection techniques through participatory observation, in-depth interviews, and documentation studies of managerial instruments such as LPLPO, stock cards, and minutes. Research informants included the Head of the Community Health Center, Pharmaceutical Technical Personnel, and Warehouse Officers. The results show that the Tamalate Community Health Center has implemented a logistics cycle in accordance with Minister of Health Regulation Number 74 of 2016. The planning stage is carried out using the consumption method using the LPLPO application. At the receiving stage, the community health center implements detailed physical verification per item although it does not use formal minutes for each transaction. Storage has implemented the FEFO and FIFO principles, supported by daily temperature monitoring, although limited warehouse space poses a physical challenge. Distribution is carried out systematically to service units, with challenges in real-time data integration. This study recommends strengthening the digitalization of stock management and optimizing storage infrastructure to ensure the efficiency of the drug supply chain in the digital health era.